Development of Comic-Based Learning Media Incorporating Riau Local Wisdom on the Topic of Characteristics of Two-Dimensional Shapes for Fourth Grade Primary School Students - Amanda, Auliya Nur; Ain, Siti Quratul (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Mathematics learning in primary schools often faces challenges related to students’ low interest and understanding, particularly in abstract topics such as the characteristics of two-dimensional shapes. This is largely due to the lack of engaging and contextual learning media suited to students’ characteristics. This study aims to explore the process and validation results of developing comic-based learning media incorporating Riau local wisdom as an alternative instructional tool for teaching the characteristics of two-dimensional shapes to fourth-grade students at SDN 194 Pekanbaru. The research adopts a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), though limited to the analysis, design, and development phases. The subjects involved six expert validators: two subject matter experts, two language experts, and two design experts. Data collection instruments included validation sheets for content, language, and design aspects. The data were analyzed using both qualitative descriptive and quantitative methods. The validation results show that the comic media was rated highly valid by subject matter experts with an average score of 86.75%, language experts 85.82%, and design experts 98%. The overall average validation score reached 90.19%, categorized as